PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATERI ATURAN MATA PELAJARAN PENDIDIKAN PANCASILA PADA SISWA KELAS 2 SDN SIDOKARE 1 SIDOARJO - Rohmah, Lailatul; Aini, Nurul; Nisyah, Choirotin; Izzudin, Muh. Aris; Asror, Machfudzil (Jurnal Muassis Pendidikan Dasar, 2026)
Based on the results of observations conducted in grade 2 of SDN Sidokare 1 Sidoarjo, there are challenges in the learning process of students, especially when they try to understand the chapter on Pancasila Education related to rules at home and at school. This study aims to improve the learning outcomes of grade 2 students at SDN Sidokare 1 Sidoarjo in the topic of rules in the subject of Pancasila Education by applying the make a match learning model. The method applied is Classroom Action Research in one cycle including the steps of planning, implementation, observation, and reflection. Participants in this observation were 12 students from grade 2 and 2 friends as observers. The findings of the study show that there is an increase in learning completeness from initially 41.67% in the pre-cycle to 83.33% in cycle I, with the average class score increasing from 68.75 to 80.42. Teacher activity was recorded at 85.29% and student activity at 88.23%, both of which are considered perfect. The conclusion of this study is that the Make A Match learning model is effective in improving students' learning achievement in the chapter on Pancasila Education rules.